Taking Action: Diversity in American Institutions - Winkler, Savannah (Kansas State University. K-State Libraries, 2016)
My project was a persuasive research paper. This paper required me to find a position on a controversial topic and persuade a resistant audience to consider my view. In addition to this, the argument needed to be multi-sided and I needed to find common ground between my view and my audience's. My topic was using affirmative action in institutions because it benefits the economy and decreases racial discrimination. My resistant audience believed the opposite.
Kirmser Undergraduate Research Award - Individual Freshman category, grand prize
Citation: Winkler, S. (2016). Taking Action: Diversity in American Institutions. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: Affirmative action; Employment Institutions; Domestic Sphere; Ideology of Separate Spheres; Women’s Role; Industrial Revolution